Peningkatan Pengetahuan pada Ibu Kader sebagai Upaya Mencegah Stunting pada Anak Balita di Puskesmas Panunggangan Kota Tangerang - Putri Ronitawati; Rachmanida Nuzrina; Yuni Paradilla Fitri; Intan Dwi Asmarani; Maria Tambunan (I-Com: Indonesian Community Journal, 2025)
Nowadays, stunting remains the most talked-about childhood growth issue. Preventing stunting in children requires a well-balanced diet rich in nutrients. A close-knit approach to the community through cadres is necessary to identify health needs and to motivate the adoption of balanced diet as a healthy lifestyle. Good health services can only be produced by cadres who possess the necessary knowledge and attitudes in the performance of their jobs. As a result, ongoing education is required. This community service project aims to raise cadre awareness of initiatives to stop toddler stunting. The Panunggangan Health Center in Tangerang City served as the location for this program. As a result of this activity, the cadre mothers' knowledge increased by 20.6% between before and after the activity. Also, our team's approach to counseling involves giving cadre moms in Panunggangan, Tangerang City, more knowledge through the use of the presenting method, which has an N-Gain value of 56.81%.